THE BINDING POWER OF GOVERMENT RULES LAWS AND RESTRICTION TO SOCIETY BASED ON CONSTITUTION (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2022)
The purpose of this research is to offer an update on the position of PPKM policies issued by the Indonesian government in a precise and binding manner. Using normative research with the aim of answering issues based on the scientific side. From this research, the researcher offers that our country adheres to a system where legal norms are tiered where a lower norm is sourced, applies, and is based on a higher norm in accordance with a hierarchical arrangement where lower regulations may not conflict with higher regulations. In the wake of the COVID-19 pandemic, the government must immediately adjust the PPKM policy with the hierarchical arrangement of laws and regulations. This is because a policy that does not have a legal instrument or forum that is not included in the category of statutory regulations has a bias binding power where this is because the PPKM policy is contained in a rule in the form of a policy regulation, not a statutory regulation.